Impact of secondary hematologic malignancies on prognosis of Hodgkin’s lymphoma survivors - Lin, Fangheng; Liu, Debin; Huang, Tao; Luo, Yunlong (Frontiers in Oncology, 2025)
BackgroundThe purpose of this study is to report the differences in the prognosis of Hodgkin’s lymphoma (HL) survivors with or without secondary hematologic malignancies (SHM).MethodsThis study included patients diagnosed with HL in the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching was used to balance the baseline differences between SHM and non-SHM patient groups, while survival analysis was used to compare the overall survival and long-term prognosis differences between the two groups.ResultsA total of 36497 patients, along with 231 matched pairs, were included in the study, with a median follow-up time of eight years. The pre-matching multivariate Cox regression results showed that the non-SHM group had a 69% higher risk of all-cause mortality compared to the SHM group. The pre-matching Landmark method revealed no difference in survival between the two groups at < 30 months; at ≥ 30 months, the mortality risk in the SHM group was higher than that in the non-SHM group (HR = 5.188, 95% CI: 3.510, 7.667, P < 0.05). After matching, the Landmark method showed that at < 50 months, the mortality risk of the SHM group was lower than that of the non-SHM group (HR = 0.629, 95% CI: 0.434, 0.935, P<0.05). At ≥ 50 months, the mortality risk of the SHM group was higher than that of the non-SHM group (HR = 3.759, 95% CI: 2.667, 5.300, P < 0.05).ConclusionThe presence of SHM significantly increases the long-term mortality risk in Hodgkin’s lymphoma survivors.